2007
DOI: 10.1111/j.1582-4934.2007.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate surfaces promote osteogenic differentiation of mesenchymal stem cells

Abstract: Although studies in vivo revealed promising results in bone regeneration after implantation of scaffolds together with osteogenic progenitor cells, basic questions remain how material surfaces control the biology of mesenchymal stem cells (MSC). We used human MSC derived from bone marrow and studied the osteogenic differentiation on calcium phosphate surfaces. In osteogenic differentiation medium MSC differentiated to osteoblasts on hydroxyapatite and BONITmatrix®, a degradable xerogel composite, within 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
160
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(180 citation statements)
references
References 47 publications
(48 reference statements)
12
160
1
1
Order By: Relevance
“…These coatings are described to induce an increased bone-to-implant contact and are regarded as osteoinductive [65]. In vitro, several studies have shown that a calcium phosphate coated implant surface promotes osteogenic differentiation of mesenchymal stem cells, which implies a stimulating effect of calcium phosphate for the formation of new bone [66][67][68].…”
Section: Cell Regulation By Chemical Characteristics Of a Materialsmentioning
confidence: 99%
“…These coatings are described to induce an increased bone-to-implant contact and are regarded as osteoinductive [65]. In vitro, several studies have shown that a calcium phosphate coated implant surface promotes osteogenic differentiation of mesenchymal stem cells, which implies a stimulating effect of calcium phosphate for the formation of new bone [66][67][68].…”
Section: Cell Regulation By Chemical Characteristics Of a Materialsmentioning
confidence: 99%
“…Calcium phosphate ceramics, especially HA, are bioactive materials capable of promoting osteogenesis of MSCs [14,47]. Substrate topography comprised of various microand nanofeatures influences cellular behavior [46].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the outcomes of other bone substitution materials like NanoBone ® and their influence on bone healing process (Gotz et al 2008), the expression of Runx2 gene was unaltered after application of BONITmatrix ® and OSSA NOVA. Otherwise BONITmatrix ® slightly increased the expression of the osteogenic transcription factor Runx2 in mesenchymal stem cells (Muller et al 2008). In addition, it was suggested that diverse forms of hydroxyapatite nanoparticles may differentially affect the osteoblast cell function as shown on gene and protein levels (Xu et al 2009).…”
Section: Composites With Different Chemical Phasesmentioning
confidence: 99%
“…Furthermore, Real-time RT-PCR analyses showed that the amount of the osteocalcin and Alpl mRNA was significantly increased after treatment with BONITmatrix ® . It was recently shown that mesenchymal stem cells differentiated to osteoblasts within 14 days on hydroxyapatite and BONITmatrix ® in expansion medium with and without osteogenic differentiation additives (Muller et al 2008). Cells revealed a higher Alpl activity and increased mRNA expression of osteocalcin and collagen 1 (Muller et al 2008).…”
Section: Composites With Different Chemical Phasesmentioning
confidence: 99%
See 1 more Smart Citation